Underwriter reputation and IPO valuation in an emerging market: evidence from Malaysia - Chui, Zi Ong; Mohd Rashid, Rasidah; Taufil Mohd, Kamarun Nisham (Emerald Publishing Limited, 2020)
Purpose – The purpose of this study is to examine the influence of underwriter reputation on the valuation of Malaysian initial public offerings (IPOs). Design/methodology/approach – This study employed cross-sectional multiple regression models to analyse the relationship between underwriter reputation and IPO valuation that included 466 IPOs listed on Bursa Malaysia from 2000 to 2017. Findings – The results revealed that underwriter reputation had a significant negative association with IPO valuation. Firms that engaged the services of reputable underwriters had their IPO offer prices set lower than the intrinsic values during the listing. After incorporating firms’ size, this study found a positive relationship between underwriter reputation and IPO valuation. Big firms (high quality) hired reputable underwriters for certification purposes as issuers were aware that the cost of hiring a reputable underwriter would be justified by increased transparency after listing. Therefore, firms that engaged reputable underwriters had approximately fair values since issuers assumed that the price would be close to the intrinsic value following enhanced transparency post-listing. Research limitations/implications – Future studies should focus on other non-financial factors, such as auditor reputation. Originality/value – The present study provides new insights into the certification role of underwriters in valuing IPOs in the Malaysian market.